KERAGAMAN GENETIK Taxus Sumatrana DARI POPULASI ALAM DI JAMBI MENGGUNAKAN PENANDA RAPD - Istiana Prihatini; Dodi Frianto; Eka Novriyanti; ILG Nurtjahjaningsih; AYPBC Widyatmoko (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2021)
The natural population of Taxus sumatrana in several regions in southern Asia including Indonesia has experienced a decline in number. In Sumatra, the population with very few trees was found in Gunung Kerinci and Gunung Tujuh, Kerinci Regency, Jambi. Conservation efforts to protect the extinction of this species are being carried out, one of which is by exploring seeds from natural populations to be planted ex situ. Information on the genetic diversity of Taxus is needed to determine a conservation strategy for this species. This researchwas conducted to obtain information on genetic diversity of Taxus sumatrana. Ten RAPD markers were used to analyze the genetic diversity of 44 individuals from two natural populations, namely Gunung Tujuh and Gunung Kerinci. These markers resulted in 104 loci which were used in the RAPD data analysis using GenAlex ver.6.5 program. The results of the data analysis showed that heterozigosity which showed the level of genetic diversity of the populations of the two populations observed was in moderate level and similar, namely 0.33±0.14 (Gunung Tujuh) and 0.35±0.14 (Gunung Kerinci). The genetic distance between the two populations was also in a moderate value (0.097) and the similarities in genetic structure based on the RAPD markers were showinggenetic variety in moderate level (0.908). The results indicate that the two populations, although geographically close have moderate level of genetic structure. Genetic conservation efforts for future Taxus species could increase the number of individuals from both locations and separate them as two distinct populations.